SAFEGUARDING PRIVACY IN SOCIAL NETWORKS - López Jiménez, David; Vargas Portillo, Patricia; Dittmar, Eduardo Carlos (Law, State and Telecommunications Review, 2020)
Purpose ”“ The purpose is to examine the degree of privacy protection in the social networking field. In this sense, we analyze the benefits of the self-regulation of the industry as a complement to the regulations. Methodology/approach/design ”“ We study the Spanish and the European regulations regarding personal data protection with respect to social networks. Findings ”“ The legislative regulations on this subject are insufficient due to their intrinsic limitations in the field. Therefore, we should encourage the approval of good legislation that complements and fills the gaps. Practical implications ”“ The advantages that are derived from the research on this subject are useful for service providers and the public and private sectors in the information society. Therefore, they are useful for society in general. Originality/value ”“ This research article includes the examination of the general utility of society. The aspects that are addressed are applicable to the industry and those who use social networks. The government must prevent infractions that damage consumers and/or users.